Large sets of large sets of Steiner triple systems of order 9 - Bryant, Darryn; Grannell, Mike; Griggs, Terry (Utilitas Mathematica, 2003)
We describe a direct method of partitioning the 840 Steiner triple systems of order 9 into 120 large sets. The method produces partitions in which all of the large sets are isomorphic and we apply the method to each of the two non-isomorphic large sets of STS(9).